Thermal Treatment and Utilisation of Sewage Sludge - Abu-Kaddourah, Ziad Mahmoud (2000)
Thermal process has become one of the major technologies for the treatment of sewage sludge to secure final products. The incinerated ash and molten slag as products of thermal treatment contain various types of heavy metals at high concentrations. Incineration and melting processes can reduce the sludge volume and stabilize the chemical compounds in the final product, which can be utilized beneficially as construction materials. In this study, dewatered sewage sludge was examined to investigate its properties when subjected to different heat treatment processes, up to the temperature of 1550 8C, in terms of chemical, physical, and micro-structure properties, degree of stabilization and the possibility of utilizing the final products in different applications. The study shows that the volume of dewatered sewage sludge reduces up to five times by the drying process, twenty times by the incineration process and fifty five times by the melting process. It was shown that heavy metals can be stabilized during the incineration process by conditioning the dried sludge with CaCO3. Heating temperature, holding time and cooling rate are the controlling parameters for the melting process, to produce different needed materials, in terms of chemical, physical, micro-structure and stability of the final products. Incinerated ash and molten slag show stable end products in terms of the leaching properties, and it is within the limit of Japanese regulation for soil environmental limit. Incinerated ash and molten slag are shown to be very good products that can be utilized as alternatives to cement and sand in concrete. By replacing 5 percent of cement with incinerated ash, the compressive strength can be improved by 50 percent compared to the standard product for the period of 3 days by getting a compressive strength of 30.80 N.mm-2. Similarly, by replacing a 50 percent of sand with molten slag, the compressive strength can be higher than the standard product for the period of 7 days with a compressive strength of26.36.